Generation Z’s Investment Interest In Indonesia’s Blockchain-Based Green Sukuk - Fitria Nurma Sari; Andy Putra Wijaya; Amrullah (Department of Islamic Financial Management, Faculty of Economics and Islamic Business, Sunan Kalijaga State Islamic University, Yogyakarta, Indonesia., 2025)
Background: As sustainable finance gains prominence, blockchain technology has emerged as an innovative tool to enhance transparency, efficiency, and trust in Islamic capital markets. Blockchain-based Green Sukuk is one of the applications in finance and has the potential to attract investment interest from Generation Z, a demographic characterized by a strong openness to innovation. Objectives: This study aims to examines the determinants of Generation Z’s investment interest in Indonesia’s blockchain-based Green Sukuk. Novelty: This study addresses the relationships between digital financial literacy, Islamic fintech, and Generation Z’s investment interest in blockchain-based green sukuk. Research Methodology / Design: This research adopts a quantitative approach, collecting survey data from Generation Z respondents with knowledge or experience in digital financial services. The study focuses on two main predictors: digital financial literacy and Islamic fintech adoption. Findings: Findings reveal that higher digital financial literacy significantly increases the likelihood of investing in blockchain-based Green Sukuk, as it equips young investors with the ability to assess risks, understand product features, and navigate digital investment platforms. Furthermore, Islamic fintech serves as an enabler by providing Sharia-compliant, user-friendly, and accessible channels for sustainable investment products. The integration of blockchain in Green Sukuk issuance is found to strengthen investor confidence by ensuring accountability and traceability of funds toward environmentally beneficial projects. Implication: The results offer practical implications for policymakers, Islamic financial institutions, and fintech providers seeking to engage younger generations in sustainable Islamic finance. By combining sustainability goals, Sharia compliance, and emerging technology, this study contributes to bridging the gap between environmental objectives and the evolving investment preferences of Generation Z in Indonesia.